Ensaios sobre património alimentar luso-brasileiro - Carmen Soares (IUC/Annablume, 2014)
They were received and adapted in the Brazilian culture. The work is organized in four parts, each one with several chapters, approaching food heritage from Classical Antiquity to the present. Part I concerns eating practices and hospitality in the Greek and Roman worlds, the two great civilization founders of Europe. The main goal of its chapters is to demonstrate that some contemporary food habits are very strongly connected to a Classical Mediterranean heritage. The underlining of these cultural bounds between nowadays food culture and its past allows us to understand the real importance of food on the shaping of everybody's cultural identity. Part II focus on food in the Middle Ages, particularly on its moral and religious issues. The social contexts considered are the king's table and the monastic communities, because those are the most well documented realities we have. Part III discusses the transition from the Middle Ages to the Modern Era, taking as example, once again, the food habits of the royal family and also of a university college. With the Portuguese Discoveries came a great impulse on sugar production and, consequently, on the manufacturing, commerce and consumption of sweets, a thematic central on this part. Part IV is dedicated to the contribution of Portuguese heritage in structuring a discourse on Brazilian cuisine and to the early appearance on the Brazilian colonial society of myths, beliefs, and taboos concerning breastfeeding (a field of research usually marginal on Food History).